2019
DOI: 10.4467/16890027ap.19.004.10835
|View full text |Cite
|
Sign up to set email alerts
|

Morpho-molecular Characterization of the Litostomatean Predatory Ciliate Phialina pupula (Müller, 1773) Foissner, 1983 (Haptoria, Lacrymariidae)

Abstract: The morphology and phylogenetic position of a haptorian ciliate, Phialina pupula (Müller, 1773) Foissner, 1983, isolated from microaerobic sandy sediments of the floodplain area of the Boise River, Idaho, U.S.A., were studied using live observation, protargol impregnation, scanning electron microscopy, and the 18S rRNA gene as well as the ITS region. The Boise population of P. pupula is characterized by a size of about 60-130 × 20-50 µm, an elliptical macronucleus with a single micronucleus, highly refractive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 39 publications
2
5
0
Order By: Relevance
“…The phylogenetic tree, based on the 18S rRNA gene, reveals unstable internal relationships and numerous weakly supported nodes within the order Spathidiida, consistent with previous reports (Chi, Wang, et al., 2021; Huang et al., 2018; Jang et al., 2017, 2022; Jiang et al., 2021; Pomahač et al., 2023; Rajter et al., 2019; Rajter & Vďačný, 2016, 2017; Vďačný et al., 2011, 2014; Yıldız, 2018). Interestingly, although Actinobolina and Papillorhabdos differ in all key features such as general appearance (ellipsoidal with numerous tentacles vs. cylindrical), extrusomes (stored in the tentacles vs. anchored to the cortex), circumoral kinety (present vs. absent), composition of somatic kineties (kinetosome clusters vs. monokinetids), and dorsal brush rows (1 vs. 4), they have an unexpectedly and fully supported phylogenetic relationship in the 18S rRNA gene tree.…”
Section: Discussionsupporting
confidence: 89%
“…The phylogenetic tree, based on the 18S rRNA gene, reveals unstable internal relationships and numerous weakly supported nodes within the order Spathidiida, consistent with previous reports (Chi, Wang, et al., 2021; Huang et al., 2018; Jang et al., 2017, 2022; Jiang et al., 2021; Pomahač et al., 2023; Rajter et al., 2019; Rajter & Vďačný, 2016, 2017; Vďačný et al., 2011, 2014; Yıldız, 2018). Interestingly, although Actinobolina and Papillorhabdos differ in all key features such as general appearance (ellipsoidal with numerous tentacles vs. cylindrical), extrusomes (stored in the tentacles vs. anchored to the cortex), circumoral kinety (present vs. absent), composition of somatic kineties (kinetosome clusters vs. monokinetids), and dorsal brush rows (1 vs. 4), they have an unexpectedly and fully supported phylogenetic relationship in the 18S rRNA gene tree.…”
Section: Discussionsupporting
confidence: 89%
“…The molecular phylogeny of Lacrymaria was initially investigated by sequencing the SSU rRNA gene of L. marina Kahl, 1933(Gao et al, 2008. Subsequently, Rossi et al (2016), Huang et al (2018), andRajter et al (2019) sequenced nine new SSU rRNA gene sequences of the genus and found that Lacrymaria was likely a non-monophyletic genus. However, none of those sequences were reported with the morphological data, which cast doubt on these results.…”
Section: A Brief Review Of the Genus Lacrymaria Bory De Saint-vincent...mentioning
confidence: 99%
“…Ciliates are excellent indicators for water quality monitoring and play a vital role in the aquatic microbial food web (Wang et al, 2022;Weisse and Montagnes, 2022). Lacrymaria ciliates are common raptorial microorganisms found in aquatic habitats worldwide (Kahl, 1930;Dragesco, 1960Dragesco, , 1965Rajter et al, 2019;Wang et al, 2019). They can be easily identified by the bubble-like head located at the front end of their body, which is covered by short oblique kineties (Lynn, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations